Denied motherhood: forced sterilisation of HIV-positive women as a violation of their human rights - Apiko, Philomena (Centre for Law and Society, 2026)
Forced sterilisation of HIV positive women has recently been focussed on in Southern Africa where reports of women who had been sterilised in government hospitals without their consent was made public.2 Sterilisation is defined as a surgical procedure whereby a person could be rendered incapable of fertilisation or reproduction3 by blocking of the sex organs.4 Forced sterilisation is sterilisation that occurs without the consent and knowledge of the patient. For the purposes of this paper forced sterilisation will include instances where the HIV-positive woman was sterilised during a caesarean section (c-section) and was not made aware of the procedure. It will also encompass instances where women were coerced against their will by health officials to undergo sterilisation.